Differential Genomic Effects of Six Different TiO2 Nanomaterials on Human Liver HepG2 Cells. Issue 7 (26th February 2016) - Thai, Sheau‐Fung; Wallace, Kathleen A.; Jones, Carlton P.; Ren, Hongzu; Grulke, Eric; Castellon, Benjamin T.; Crooks, James; Kitchin, Kirk T.
ABSTRACT: Human HepG2 cells were exposed to six TiO2 nanomaterials (with dry primary particle sizes ranging from 22 to 214 nm, either 0.3, 3, or 30 μg/mL) for 3 days. Some of these canonical pathways changed by nano‐TiO2 in vitro treatments have been already reported in the literature, such as NRF2‐mediated stress response, fatty acid metabolism, cell cycle and apoptosis, immune response, cholesterol biosynthesis, and glycolysis. But this genomic study also revealed some novel effects such as protein synthesis, protein ubiquitination, hepatic fibrosis, and cancer‐related signaling pathways. More importantly, this genomic analysis of nano‐TiO2 treated HepG2 cells linked some of the in vitro canonical pathways to in vivo adverse outcomes: NRF2‐mediated response pathways to oxidative stress, acute phase response to inflammation, cholesterol biosynthesis to steroid hormones alteration, fatty acid metabolism changes to lipid homeostasis alteration, G2/M cell checkpoint regulation to apoptosis, and hepatic fibrosis/stellate cell activation to liver fibrosis.